The Effect of Study Tour Activity in Teaching Junior High School Students Speaking Skill. - Muhammad Fauzi Bafadal; ilham Ilham (Linguistics and ELT Journal, 2018)
The study tour is emphasized experiential learning and offer both group and self-directed activities that enable learners to explore new territories, cultures, and people. The study tour is designed to be both fun and educational. Study tour activity helps the students develop all four languages skills in real life, and make speaking activities more effective. In order, the purpose is to investigate study tour activity affects or not in teaching speaking skill at the first Grade of Islamic Junior High School, Al-Maarif Tumpak, District of Pujut. The subject of this study was conducted in the first-grade students’ of Islamic Junior High School Al-Maarif Tumpak. This study used purposive sampling. The writer took 25 students as a sample that divided into two groups, 13 students belong to the experimental group, and 12 students belong to the control group. In collecting the data, this study used pre-test post-test as the research instrument then followed by analyzing the data using the t-test formula. This study found that the mean score of post-test of the experimental group is higher than the control group. It means that study tour activity affects teaching speaking skill. An analyzing data from the result between the deviations of mean scores of the experimental group was 28,9 and control group was 21,7. Then the result of the statistical analysis of t-test in this study was 2,09. It was higher than critical values for t-table in the degree of freedom (df) 23 is 2, 069 (0, 05%). Based on the result of this study, the alternative hypothesis (Ha) is accepted.